Optimizing the Role of the Regional House of Representatives (DPRD) Deliberative Bureau: A Systematic Literature Review - Tartib, Muhammad; Etty Sri Wahyuni (Open Access Indonesia Journal of Social Sciences, 2023)
The Deliberative Bureau (Banmus) plays an important role in ensuring the smooth and effective work of the DPRD in making quality decisions. Optimizing the role of the DPRD Deliberative Bureau has great significance in improving the quality of legislative performance at the regional level. This study seeks to do discussion various steps and strategies that can be taken to optimize the role of the DPRD Deliberative Bureau. The literature search process was carried out on various databases (PubMed, Web of Sciences, and Google Scholar) regarding optimizing the role of the consultative bureau of the Regional House of Representatives. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Efforts to optimize the role of the DPRD Deliberative Bureau can be made in a number of ways, namely: strengthening the role of legislation by increasing the capacity of members of the DPRD Deliberative Bureau in drafting and supervising regional regulations (perda), as well as involving stakeholders and the public in the perda-making process through dialogue and public consultation. Increasing the understanding of members of the DPRD Deliberative Bureau about the political system, democratic principles, and legislative tasks through political education programs, carrying out their duties in a transparent and accountable manner through mechanisms such as live broadcasting of the DPRD Deliberative Bureau meetings, regular publication of activities, providing access to information to the public, and establishing a complaint mechanism and handling complaints from the public. Increasing cooperation and synergy between the DPRD Deliberative Bureau and local government through the establishment of working groups, coordination meetings, dialogue forums, and synergy in regional development planning and budgeting. Carry out the oversight function more effectively through the mechanism of routine monitoring meetings, field visits, local government performance audits, inquiries, and interpellations, as well as reporting mechanisms and complaints from the public.